PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF DAN PROFIL PELAJAR PANCASILA SISWA SMK BINA INSANI KABUPATEN HALMAHERA BARAT - Negraha, Eka Ayu; Tuara, Narilah A (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
This research aims (1) to find out how the application of the Project Based Learning model can improve the cognitive learning outcomes of class West Halmahera. This research uses the Classroom Action Research (PTK) method. The research subjects were 26 class X students of Bina Insani Vocational School. The research results show that (1) The application of the Project-Based Learning (PjBL) model has proven effective in improving the cognitive learning outcomes of class X students at Bina Insani Vocational School. In cycle I, 65.39% of students achieved completion with an average score of 72.12, although there were still 34.61% of students who had not completed it. However, in cycle II, there was a significant increase, with 96.15% of students achieving completeness and an average score of 78.08, showing the effectiveness of PjBL in increasing economic understanding. The PjBL model has also succeeded in increasing student creativity, especially in the Pancasila Student Profile aspect. In cycle I, student creativity was seen in the analysis of family economic cases, although several aspects such as elaboration and creative problem solving were still less than optimal. Cycle II showed a significant increase in creativity, with students generating original ideas, conveying alternative solutions fluently, and being able to see problems from various perspectives. Collaboration and creative exploration also increase, demonstrated through high-quality final reports.